2001
DOI: 10.1161/hy1201.096056
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Cardiovascular Effects of Liposome-Entrapped Angiotensin-(1-7) at the Rostral Ventrolateral Medulla

Abstract: Abstract-The aim of this work was to evaluate the potential of liposomes as a tool for the sustained release of the short half-life peptides of the renin-angiotensin system in a specific site of the brain. Angiotensin (Ang)-(1-7) was selected for this study because of its known cardiovascular effects at the level of the rostral ventrolateral medulla (RVLM) and because of the considerable interests in elucidating its physiopathological role as a neuromodulator. Ang-(1-7)-containing liposomes (LAng) were microin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 26 publications
(35 reference statements)
0
50
1
Order By: Relevance
“…Central Ang-(1-7) is involved in regulation of sympathetic outflow and cardiovascular activity. 24,38 Dense Mas receptor immunoreactivity is found in the RVLM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Central Ang-(1-7) is involved in regulation of sympathetic outflow and cardiovascular activity. 24,38 Dense Mas receptor immunoreactivity is found in the RVLM.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that Ang-(1-7) in the RVLM enhances the CSAR and increases the sympathetic outflow and blood pressure via Mas receptor activation. The increased endogenous Ang-(1-7) and Mas receptor activity in RVLM contributes to the enhanced CSAR and sympathetic activation in renovascular hypertension, and the cAMP-protein kinase A pathway is involved in these Ang-(1-7)-mediated effects 24,30,31 Our recent study has shown that Ang-(1-7) in the RVLM enhances the CSAR and increases renal sympathetic nerve activity (RSNA) and mean arterial pressure (MAP), whereas A-779 microinjection into the RVLM decreases the RSNA and MAP and inhibits the CSAR in normal rats.32 However, it is not known whether Ang-(1-7) in the RVLM is involved in the enhanced CSAR and excessive sympathetic activation in hypertension.A recent study demonstrates that Mas receptor activation by Ang-(1-7) increases the intracellular cAMP level and activates protein kinase A (PKA) and that inhibition of either adenylyl cyclase (AC) or PKA activity attenuates Ang-(1-7)-induced extracellular signal-regulated kinase 1/2 activation in glomerular mesangial cells.33 Ang-(1-7) inhibits vascular growth via prostacyclin-mediated cAMP production and PKA activation. 34 These results demonstrate that the cAMP-PKA signaling pathway regulates Ang-(1-7) function in some peripheral tissues.…”
mentioning
confidence: 99%
See 3 more Smart Citations